A Political Agency Theory of Central Bank Independence - Eggertsson, Gauti B. (2012)
We propose a simple theory to explain why, and under what circumstances, a politician delegates policy tasks to a technocrat in an independent institution and then analyze under what conditions delegation is optimal for society. Our theory builds on Holmstrom's (1982, 1999) "hidden effort" principal-agent model. The election pressures that politicians face, and the absence of such pressures for technocrats, give rise to a dynamic incentive structure that formalizes two rationales for delegation, one highlighted by Hamilton (1788) and the other by Blinder (1998). Delegation trades off the cost of having a possibly incompetent technocrat with a long-term job contract against the benefit of having a technocrat who (i) invests more effort into the specialized policy task and (ii) is better insulated from the whims of public opinion. A natural application of our framework suggests a new theory of central bank independence.